Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part XVII. Writing and Printing Papers from Castor Stems (Ricinus gommunis, Linn) - Bhat, R. V.; Jaspal, Narendra S. (Indian Forester, 1953)
Pilot plant experiments on the production of writing and printing papers from castor stems are described. The pulps were prepared by the sulphate process. Since castor stems are short-fibred, 30% bamboo pulp was blended with their pulp in the manufacture of papers. The papers were characterized by good formation and satisfactory strength properties. Two samples of papers are appended in this bulletin. One is a writing paper and the other is a printing paper.